(untitled) (Research, Society and Development, 2022)
In today’s article, in the face of caressing and concern for animal life, we tended to discuss, as a general objective, the factors that occasionally contribute to cruelty to the detriment of animals. From this, the specifics emerged, consisting of briefly contextualizing the historical evolution regarding the legal achievements of animals, producing a technical analysis of a material and procedural nature of Brazilian animal law and investigating what motivates and what results in animal cruelty and helplessness in a legal, procedural, administrative and social context. This article developed a bibliographic survey through the reading and analysis of authors who debate on the topic. To obtain the present data, published books, magazines, articles and periodicals were consulted. In summary, the results, coming from the law, from the procedural application, those of an administrative and social nature, proved to be quite sufficient, to the point of elucidating the reasons why this scenario had stagnated and became "normal", because, what, in short, occurs in practice, is that such cruel conducts are not rebutted in the way they deserve. Which, notoriously, only alerts the urgency with which this scenario deserves to change, considering that, because animals configure sentient beings, so to speak, they have sensations, sensitivity, physical and mental suffering, criminal conduct, which torture, hurt, leave sequelae (sometimes irremediable) cannot simply be overlooked, or even treated - legally, procedurally, administratively and socially - with such disinterest and carelessness.